Biogas: Opportunities to Improve Safety and Safety Regulation - Salvi, Olivier; Chaubet, Christine; Evanno, Sébastien (Transactions of the VŠB-Technical University of Ostrava, Safety Engineering Series, 2012)
The production of biogas is positioned as energy which can not only generate a source of renewable energy but also which recycles waste. In the context of sustainable development, the place of biogas is therefore essential. Several questions about safety issues, the harmonization of the regulations and the need to develop standards are discussed in this paper, based on the results of a workshop on biogas safety and regulation organized in November 2010 and the activities of the European Working Group on Biogas Safety and Regulation created after the workshop. The risks corresponding to the biogas production and use have been framed using iNTeg-Risk method and tools. Several defi cits for risk management have been identifi ed and a strategy to improve risk management proposed by the working group is presented at the end of the paper.